The Lutheran Church in Ukraine: in search of a national identity - Victoria LYUBASHCHENKO (Богословські роздуми: Східноєвропейський журнал богословʼя)
The unique characteristics of Lutheranism in comparison with other Protestant churches in the historical-cultural context of Ukraine are analyzed in this article. The main attention is given to the problem of the Lutheran Church’s adaptation to the religious national traditions of Ukraine, shown in the examples of three Lutheran communities: the German Evangelical-Lutheran Church of Ukraine, the Association of Evangelical Lutheran Brethren Congregations of Ukraine, and the Ukrainian Lutheran Church. The process of synthesizing Lutheran doctrine and the Orthodox rite, which the Ukrainian Lutheran Church is attempting to carry out, is also shown.